Multi Document Summarization using Cross Document Relations - Desai, Yogita; Rokade, PP (International Journal of Computer Sciences and Engineering, 2025)
Multi-document summarization refers to the process of automatic extraction of text from multiple sources which belong to same topic. With the increase in usage of internet large amount of data has been generated day by day. It is quite difficult for anyone to distinguish and summarize this vast information gathered from various sources. Multi document text summarization has solution for this problem. Multi document summarization assembles information from different sources and summarizes the information up to necessary length. In this paper preprocessing is applied to unprocessed documents and different features are extracted. And then CST relations are identified from these extracted features document. Finally summary is generated depending on identified CST relations.